2013
DOI: 10.3109/17453674.2013.785908
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific guide for revision of medial unicondylar knee arthroplasty to total knee arthroplasty

Abstract: Background and purpose Unicompartmental to total knee arthroplasty revision surgery can be technically demanding. Joint line restoration, rotation, and augmentations can cause difficulties. We describe a new technique in which single-way fitting guides serve to position the knee system cutting blocks.Method Preoperatively, images of the distal femur and proximal tibia are taken using CT scanning. These images are used to create a patient-specific guide that fits in one single position on the contours of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Apart from orthopedics (guides for knee arthroplasties), 3D-printed surgical guides were also used in neurosurgery, dental surgery, spinal surgery, and maxillofacial surgery. 28 of the 53 studies that mentioned reduced operation room time also supported this claim with numbers or statistics [ 39 , 74 , 81 , 84 , 118 , 131 , 132 , 135 , 136 , 140 , 141 , 145 , 151 , 152 , 162 , 175 , 177 , 181 , 190 , 194 , 196 , 200 , 207 , 210 212 , 219 ]. Increased procedural time was seen in seven papers, of which five supported this with numbers or statistics [ 62 , 73 , 125 , 143 , 153 , 161 , 225 ].…”
Section: Resultsmentioning
confidence: 87%
“…Apart from orthopedics (guides for knee arthroplasties), 3D-printed surgical guides were also used in neurosurgery, dental surgery, spinal surgery, and maxillofacial surgery. 28 of the 53 studies that mentioned reduced operation room time also supported this claim with numbers or statistics [ 39 , 74 , 81 , 84 , 118 , 131 , 132 , 135 , 136 , 140 , 141 , 145 , 151 , 152 , 162 , 175 , 177 , 181 , 190 , 194 , 196 , 200 , 207 , 210 212 , 219 ]. Increased procedural time was seen in seven papers, of which five supported this with numbers or statistics [ 62 , 73 , 125 , 143 , 153 , 161 , 225 ].…”
Section: Resultsmentioning
confidence: 87%
“…They concluded that mechanical alignment can easily be obtained with PSI technology by intra-articular correction of deformities under 20°. Kerens et al used PSI for revision of medial uni-condylar knee arthroplasty to TKA 41 . Seven of 10 femoral prostheses were within the desired AP and sagittal angles of ±3°, all tibial components were within the desired AP angle of ±3°and 7 of 10 were within the desired sagittal angle.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that many authors propose PS preoperative preparation for "difficult" cases (e.g. severely comminuted fractures or cranial base tumours [49] Complete clearance of stones 5/8 (62.5%) -Mucosal perforation 1/8 (12.5%) Gateno et al [20] Deformities corrected at 6 week f/u Xia et al [27] NIP Hislop et al [44] Successful operations (0% residual vessel stenosis) 3/5 (60%) Lu et al [53] 77.8% improvement in symptoms at 9 months f/u No complications Ng et al [47] Complete resection 23/23 (100%) -4.3% had additional neurological deficit post-operatively -1/23 severely disabled due to post-operative complications Dhanda et al [17] 1.43 cm average improvement in mouth openining Fornaro et al [29] Anatomic or satisfactory reduction of fracture 7/7 (100%) -No serious complications Qiu et al [43] Total tumour resection 33/45 (73.3%) -Decrease >10% of effective fibre of pyramidal tract 7/45 (15.6%) Dong et al [28] Resection margins free of tumour in all cases Essig et al [18] 2/3 good results Ferrari et al [48] No Information Provided (NIP) Hu et al [31] NIP Tepper et al [7] NIP Derand et al [16] Surgeons' opinion: Good correlation of plan and surgical steps Calculated reduction in operation time 30min Kanzaki et al [54] No conversion to open Margins free of cancer 3 complicationsprolonged air leak, needed pleurodesis Kerens et al [33] All guides fitted well during real surgery Good stability in all cases at 6 weeks f/u No complications Nam et al [9] Good alignment of lower limb for: CAS: 92.7% -PCS:70.7% Scolozzi [25] Satisfactory reconstruction 2/2 0 complications Shen et al [37] Satisfactory or anatomical reduction in 5/6 (83.3%) cases -No complications (0%) Willaert et al [45] NIP Adolphs et al [14] NIP Desender et al [41] NIP Hsu et al [21] NIP Issa et al [32] No complications Mandel et al [57] NIP Pietsch et al [35] Satisfactory outcome (overall axis within 3 o ) 47/51 (94%) Schweizer et al [36] Improvement of wrist ROM at 1 year f/u Increase of wrist strength by 10% on average No complications (no ...…”
Section: Surgeons' Feedbackmentioning
confidence: 99%